STRUCTURAL TRANSFORMATION OF 2:1 DIOCTAHEDRAL LAYER SILICATES DURING DEHYDROXYLATION-REHYDROXYLATION REACTIONS - Muller F.; Drits V.; Plancon A.; Robert J.L. (My University, 2000)
The structural transformation of dioctahedral 2:1 layer silicates (illite, montmorillonite, glauconite, and celadonite) during a dehydoxylation-rehydroxylation process has been studied by X-ray diffraction, thermal analysis, and infrared spectroscopy. The layers of the samples differ in the distribution of the octahedral cations over the cis- and trans-sites as determined by the analysis of the positions and intensities of the 11l, 02l reflections, and that of the relative displacements of adjacent layers along the a axis (c cos β/a), as well as by dehydroxylation-temperature values. One illite, glauconite, and celadonite consist of trans-vacant (tv) layers; Wyoming montmorillonite is composed of cis-vacant (cv) layers, whereas in the other illite sample tv and cv layers are interstratified. The results obtained show that the rehydroxylated Al-rich minerals (montmorillonite, illites) consist of tv layers whatever the distribution of octahedral cations over cis- and trans-sites in the original structure. The reason for this is that in the dehydroxylated state, both tv and cv layers are transformed into the same layer structure where the former trans-sites are vacant. The dehydroxylation of glauconite and celadonite is accompanied by a migration of the octahedral cations from former cis-octahedra to empty trans-sites. The structural transformation of these minerals during rehydroxylation depends probably on their cation composition. The rehydroxylation of celadonite preserves the octahedral-cation distribution formed after dehydroxylation. Therefore, most 2:1 layers of celadonite that rehydroxylate (~75%) have cis-vacant octahedra and, only in a minor part of the layers, a reverse cation migration from former trans-sites to empty octahedra occurred. In contrast, for a glauconite sample with a high content in (IV)Al and (VI)Al the rehydroxylation is accompanied by the reverse cation migration and most of the 2:1 layers are transformed into tv layers.